From literal dreams to metaphorical dreaming: art, rhetoric, and self-creation. Issue 1 (2nd January 2020) - Martin, Aaron; Eisele, Gianna; Hogg, Ian; Neal, Hannah; Shukr, Amal
Abstract : The rhetorical shifts used to capture oneiric experiences can materialize into a real-life shift between the imaginative and the experiential. By taking a Rortyan approach to the conception of the unconscious, this essay seeks to examine the ways in which the metaphorical and linguistic attachments to dreaming can help guide one's own self-representation – that is, dreams become vehicles of creation. After tracing the semantic development of dreams, the essay surveys how dream-inspired art can transmit to and through lived experiences, as seen in examples from history. Then, by advancing the pervasiveness of the metaphorical dream, namely through analyzing expressions like the 'American Dream, ' the essay turns to demonstrate how these pervasive metaphors can materialize into shared experiences. Such experiences can transcend metaphorical boundaries by fostering a representation far beyond mere fantasy toward a calculated self-creation.